the effectiveness of the SCAMBER program in developing creative thinking among students of the National Center for the distinguished- semi –experimental stady in Lattakia (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The study main to know the effectiveness of the SCAMBER  program in developing creative thinking among students of the National Center for  the distinguished. The original community to research all the tenth -grade secondary students included the National Center for Excellence in Lattakia, and the first division consisting of (40) students was chosen to be the research sample, and the research is followed by the semi -experimental curriculum, and the research used the Torrance test for creative thinking the verbal image of the form ( A).The search results showed that there are teams with statistical significance at the level of significance (0.05) between the average degrees of the experimental group members and between their average degrees in the post application on the Torrance test for creative thinking with skills (fluency- flexibility- originality- details) and the overall degree of these skills, in favor of the post application This means the effectiveness of the Skambir program in developing creative thinking among students of the National Center for Excellence.
Keywords: 1- SCAMBER program 2- Creative Thinking 3- Students of the National Center for Excellence